Autobiographical memory and the construction of a narrative self : developmental and cultural perspectives - Fivush, Robyn; Haden, Catherine A. (L. Erlbaum, 2003)
Divided into three parts, this volume discusses: the development of autobiographical memory and self-understanding; cross-cultural variation in narrative environments and self-construal; and the construction of gender and identity concepts in developmental and situational contexts.